Status Gizi, Aktivitas Fisik dan Produktivitas Kerja Karyawan Tambang Batu Bara PT. Kaltim Prima Coal: Nutritional Status, Physical Activity and Work Productivity of Coal Mining Employees of PT. Kaltim Prima Coal - Zahra, Yasmeen Aulia; Riyadi, Hadi; Zahra, Yasmeen Aulia Zahra (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2022)
Work productivity is the ability of a person or group of people to produce goods or services. Increasing work productivity is required so that the employees can have more efficient, effective, and productive performance. Nutritional status is one aspect of occupational health that has an important role in terms of work productivity. The purpose of this study was to analyze the relationship between nutritional status and work productivity of coal mining employees of PT. Kaltim Prima Coal. The research design was cross-sectional and involved 95 subjects. Data collection was carried out using google forms and telephone interviews. Subjects aged 26–55 years with most (63%) had good nutritional status. The average subject's level of physical activity was relatively light on weekdays (54%) and weekends (40%). The average level of energy and nutrient adequacy of the subject was still relatively low on weekdays and weekends. Analysis of differences in employee nutritional adequacy levels showed that there was no significant difference between weekdays and weekends (p>0.05). The level of physical activity of the subjects showed that there were differences on weekdays and weekends, especially for the level of heavy physical activity (p<0.05). The results of the correlation test showed that there was no significant relationship between physical activity and nutritional status (p>0.05) and there was also no significant relationship between nutritional status and work productivity (p>0.05).